Practical healthcare self-massage along meridians and acupoints ([China] : Foreign Languages Press, 2007)
Contiene paso a paso las demostraciones para siete tipos de técnicas de masaje para diferentes partes del cuerpo que aumentan el flujo sanguíneo y la circulación.
Contiene : Self-massage along meridians and acupoints for strengthening the body and prolonging life. Self-massage along meridians and acupoints of the face for enhancing apperance. Self-massage along meridians and acupoints for health of the breasts. Self-massage along meridians and acupoints for cleaning and strengthening teeth. Self-massage along meridians and acupoints for health of the abdomen. Self-massage along meridians and acupoints for losing weight.Self-massage along meridians and acupoints for health of the knees.
Con pistas de sonido en inglés y chino
Keywords: MASAJE